Star formation history of stellar systems in NGC 1316 - Sesto, Leandro Alberto (2021)
Galaxy mergers are often considered in the literature as ideal places to study diverse starburststriggered during the merger events. In that sense, the intermediate-age merger remnant NGC 1316 constitutes a perfect case to study complex large-scale star formation events in the Local Universe. In a series of previous works we confirmed the existence of a complex globular cluster (GC) system associated with NGC 1316, which is dominated by the presence of an unusual young (≈ 2.1 Gyr) and metal-rich subpopulation (−0.5 < [Z/H] <0.5 dex), possibly created during the last merger event. In this work we used high-quality spectroscopic data from Gemini/GMOS to present an analysis of the the star formation history of three GCs associated to this galaxy. Although recent works show the presence of multiple stellar populations in old GCs in the Milky Way and nearby galaxies, this project constitutes one of the first studies to show multiple stellar populations in young extragalacticGCs.